Tobacco farmers and diversification: opportunities and barriers. Issue 3 (1996) - Altman, D G; Levine, D W; Howard, G; Hamilton, H
Abstract : OBJECTIVE: To assess the knowledge, attitudes, and behaviours of tobacco growers and allotment owners in the southeastern United States. DESIGN: Cross-sectional telephone survey. PARTICIPANTS: Tobacco growers (n = 529) and tobacco allotment owners (n = 417) were interviewed by telephone in March 1995. SETTING: Tobacco growing states in the southeastern US. MAIN OUTCOME MEASURES: Attitudes of tobacco growers and tobacco allotment owners towards, and experience with, diversification; and attitudes towards an increase in the federal excise tax on tobacco. RESULTS: Half of the respondents had done something to learn about on-farm alternatives to tobacco, had an interest in trying other on-farm ventures to supplement tobacco income, and found alternatives that were profitable. There was a strong, negative linear trend between age and being interested in or trying alternative enterprises. Structural and economic impediments to diversification were noted by respondents (especially younger respondents), but 73% supported an increase in the federal excise tax on tobacco if the money was used to help farmers overcome these barriers. CONCLUSIONS: These data suggest that farmers and health professionals have reason to establish dialogue around diversification and using excise tax increases to fund diversification and to promote health. Tobacco companies have been successful in mobilising farmers against tax increases, but efforts must be made to show farmers that tax increases can be beneficial both to their diversification efforts and to public health. The outcome of this dialogue may well affect the economic infrastructure of thousands of rural communities, the livelihood of tens of thousands of tobacco farmers and their families, and the health of millions of tobacco users.